“Eu como general do mato já não estranho viver a sertanista” : a trajetória de D. António Rolim de Moura na Capitania de Mato Grosso através de suas cartas (1751-1764) - Ferreira, Débora Cristina dos Santos (2021)
In 1748, D. António Rolim de Moura has received at the mercy of governing the Capitania de Mato Grosso, his instructions consisted a foundation a village in the Guaporé Valley and guard the Portuguese domains of the Castilian threat, populating and consolidating the border in process of the demarcation by Madrid Treaty. From a noble origin, Rolim de Moura built the military career, until occupy the position of vedor da Casa da Rainha. His services and networks integrated the West Border. The present thesis investigates a D. António Rolim de Moura trajectory under his government in the Capitania de Mato Grosso with letters he sent to different persons. We search the narrative strategy that author employed to demonstrate his services to Majesty.